2023
DOI: 10.3390/coatings13010197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Process Parameters on Microstructure and High-Temperature Oxidation Resistance of Laser-Clad IN718 Coating on Cr5Mo Steel

Abstract: Cr5Mo steel with high thermal strength is frequently applied as the material for hydrocracking furnace tubes. Nonetheless, Cr5Mo tubes are prone to material failure in a high-temperature environment, threatening production safety. Considering that the IN718 nickel-base superalloy has favorable high-temperature oxidation resistance, the IN718 coating was fabricated on Cr5Mo substrate through laser cladding. The effect of process parameters on the high-temperature oxidation resistance of laser cladding IN718 coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…As the laser power increases, martensitic hardening and carbide precipitation occur, which leads to an increase in the microhardness of the cladding coating. Zelin Xu et al [18] analyzed the influence of process parameters on the microstructure and high-temperature oxidation properties of IN718 laser cladding coatings. The results showed that the laser power and scanning speed have an influence on the eutectic precipitation, and the eutectic precipitation is positively correlated with the mass gain of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…As the laser power increases, martensitic hardening and carbide precipitation occur, which leads to an increase in the microhardness of the cladding coating. Zelin Xu et al [18] analyzed the influence of process parameters on the microstructure and high-temperature oxidation properties of IN718 laser cladding coatings. The results showed that the laser power and scanning speed have an influence on the eutectic precipitation, and the eutectic precipitation is positively correlated with the mass gain of the coating.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have produced a significant amount of research on high-temperature protection coatings of nickel and nickel alloys, including the selection of coating materials [7,8], coating preparation [9,10], coating modifications [11,12], properties [13,14], and oxidationresistance mechanisms [15,16]. These research results have promoted the development of high-temperature protection fields and also provided guidance for the development of this project.…”
Section: Introductionmentioning
confidence: 99%